Investigations on the Performance of a Novel Semi-active Tuned Liquid Column Damper. (2017) - Altay, Okyay; Nolteernsting, Felix; Stemmler, Sebastian; Abel, Dirk; Klinkel, Sven
Abstract: A semi-active tuned liquid column damper (S-TLCD) is proposed, which can tune both the natural frequency and the damping ratio autonomously. The S-TLCD reaches a robust high-level damping performance by adapting its parameters to the changing loading and structural conditions. Degradation effects, soil-structure interaction and environmental variations can cause such changes. This paper summarizes the results of the numerical and experimental investigations on the performance of the damper. For the numerical analyses, a seismically excited 20-story benchmark building is used. The calculation results are compared with a passive tuned mass damper (TMD). Due to its adaptation capacity, the S-TLCD shows a higher performance regardless of the fluctuations in the natural frequency of the building. On the experimental part of the study, the frequency change capacity of the S-TLCD is also documented by using shake table tests and comparing the results with the analytical solutions.